The Relationship Between Peer Support and Stress Levels Among University Students - Supriadi, Nadia Nur Rozbiah; Maryama, Nina; Hermawati, Irma; R N, Nur Azizah; Hidayat, Rahmat (KIAN JOURNAL, 2024)
Objective: This study aimed to examine the relationship between peer support and stress levels among university students. Methods: A cross-sectional study was conducted from March to April 2025 involving 35 undergraduate students selected through purposive sampling at Institut Kesehatan Rajawali Bandung. Peer support was measured using a validated questionnaire covering informational, instrumental, emotional, and appraisal support. Stress levels were assessed using the stress subscale of the DASS-42. Data were collected via an online survey and analyzed using the Chi-Square test with SPSS version 29. Results: Most participants reported fair (74.3%) or good (25.7%) levels of peer support. Stress levels were predominantly normal (45.7%) or mild (28.6%). The statistical analysis showed no significant relationship between peer support and stress levels (p = 0.698) Conclusion: Although peer support is generally considered beneficial for mental health, this study found no significant association between peer support and stress levels among university students. Broader factors such as academic pressure and individual coping mechanisms may play a more influential role, suggesting the need for comprehensive support strategies in higher education.